Técnicas de diagnóstico mcmaster e mini-flotac na quantificação de oocistos e ovos de parasitos gastrintestinais de ovinos - Lima, Maria de Lara Oliveira (Universidade Federal Rural do Semi-Árido, 2019)
The Brazilian Northeast has a highlight for sheep production due to the rusticity and adaptability of the animals to the climate and vegetation. However, the gastrointestinal parasitosis in these animals causes great economic losses. The clinical diagnosis of helminth infections in small ruminants is not always possible, although many clinical signs are indicative of high parasitic load. In order to prevent serious problems in this productive sector, it is necessary to use sensitive and specific diagnostic techniques for gastrointestinal infections in these animals. Considering the great productive loss of ovine breeding in detriment of parasitism in the region of Mossoró, RN, the study aimed to verify diagnostic techniques for quantification of eggs and oocysts of gastrointestinal parasites in sheep from this region. Stool samples from 45 naturally infected sheep without anthelmintics were used for at least 90 days. The feces were collected directly from the rectal ampulla, stored individually in plastic bags, placed in an isothermal box and sent to the Animal Parasitology Laboratory of the Federal Rural Semi-Arid University (UFERSA) for analysis. They were submitted to four diagnostic methods, among them the techniques of egg count per gram of feces (OPG) with McMaster, according to Gordon and Whitlock (1998), with modification of Chagas, Niciura and Molento (2011), being called McMaster100 and McMaster25, respectively; and the modified Mini-FLOTAC technique of Rinaldi et al. (2014) and Cringoli et al. (2017), called Mini-FLOTAC10 and Mini-FLOTAC5. Oocysts and eggs were identified through morphology and with the aid of specific taxonomic keys. The data obtained were submitted to the statistical program SPSS version 21.0 and the statistical differences and agreement between the techniques, by Friedman (p <0.05) and kappa (p-value), respectively. Values of (p <0.05) were considered significantcy, were identified eggs of the type Strongyles, Strongyloides spp., Moniezia spp., Trichuris spp., besides oocysts of Eimeria spp. For Eimeria spp., the techniques of McMaster100 and Mini-FLOTAC10 presented greater potential for oocyst recovery. For Strongyles there was no difference between the techniques regarding their potential for egg retrieval. The McMaster100 presented greater potential in the recovery of eggs of the type Strongyloides spp. Eggs of Moniezia spp. and Trichuris spp. were only retrieved by Mini-FLOTAC5. When performing the analysis of agreement between the techniques studied, it was observed that they present a high degree of agreement between them, being statistically similar. The use of more than one technique for coproparasitological diagnosis is indicated, since the only one method may not reveal the true parasitism, especially considering that, in many cases, the animals present co-infections.
Monografia
Keywords: Exames coproparasitológicos; Pequenos ruminantes; Mossoró/RN; Helmintos; CIENCIAS AGRARIAS::MEDICINA VETERINARIA